Observation of Water-Droplet Impacts with Velocities of O(10 m/s) and Subsequent Flow Field. (11th August 2015) - Tatekura, Y.; Fujikawa, T.; Jinbo, Y.; Sanada, T.; Kobayashi, K.; Watanabe, M.
Abstract : A two-fluid spray cleaning technique has been gaining popularity as a cleaning process in the semiconductor industry. The most essential physical process in this technique is the impact of droplets with a velocity of O (10 m/s) on a solid surface. This study aims to experimentally and numerically investigate water-droplet impacts with velocities of up to 50 m/s and their subsequent flow fields, especially the gas flow field in the strictly limited area in the vicinity of the contact line. First, we experimentally evaluated the velocity of the splash and numerically calculated the gas velocities. Comparison of these velocities supported our assumption that the maximum gas velocity may be on approximately the same order as the velocity of the splash. Therefore, we concluded that the gas velocity field of the order of 500 m/s indeed develops at the impact of droplet with a velocity of the order of 50 m/s. Moreover, we determined that the gas pressure was of the order of 1.0 MPa by numerical analysis. Such a high pressure leads to shock wave propagation, which can contribute to the cleaning process in semiconductor production.